2020
DOI: 10.2147/opth.s261565
|View full text |Cite
|
Sign up to set email alerts
|

<p>Cystoid Macular Edema Following Cataract Surgery with Low-Energy Femtosecond Laser versus Conventional Phacoemulsification</p>

Abstract: To compare postoperative changes in central subfield macular thickness (CSMT) and prevalence of cystoid macular edema (CME) in patients undergoing cataract surgery with low-energy femtosecond laser versus standard phacoemulsification. Design: This was a retrospective comparative real-world study. Methods: Postoperative data of 252 eyes of 165 patients were collected: 138 eyes received low-energy femtosecond laser-assisted cataract surgery (FLACS) and 114 eyes underwent conventional phacoemulsification cataract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 35 publications
1
8
1
1
Order By: Relevance
“…44 Low-energy femtosecond laser that we used, has been reported to produce no meaningful increase in prostaglandin levels in the aqueous humor. 45 Recently, Van Nuffel et al 23 reported that FLACS with low-energy femtosecond laser and conventional surgery were comparable with regard to the changes in mean CRT and the occurrence of macular edema, although the low-energy FLACS induced a trend toward lower rates of macular edema.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…44 Low-energy femtosecond laser that we used, has been reported to produce no meaningful increase in prostaglandin levels in the aqueous humor. 45 Recently, Van Nuffel et al 23 reported that FLACS with low-energy femtosecond laser and conventional surgery were comparable with regard to the changes in mean CRT and the occurrence of macular edema, although the low-energy FLACS induced a trend toward lower rates of macular edema.…”
Section: Discussionmentioning
confidence: 98%
“…19,21 In contrast, low-energy femtosecond lasers have been associated with less inflammatory response and collateral ocular damage. 22,23…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analysis data have shown that there was no significant difference in the incidence of CME between FLACS and conventional phacoemulsification (23), which is in alignment with our study. Nuffel et al further evaluated the changes in the central subfield macular thickness in low-energy FLACS vs. conventional surgery and reported no statistically significant difference (37).…”
Section: Discussionmentioning
confidence: 99%
“…It is yet unknown what clinical effect inflammation caused by FLACS has because it is reported that cases done with femtosecond laser does not result in greater PCME when compared with conventional phacoemulsification [26,27 ▪ ,28].…”
Section: Inflammation During and After The Cataract Surgerymentioning
confidence: 99%